2018
DOI: 10.3389/fendo.2018.00099
|View full text |Cite
|
Sign up to set email alerts
|

Serum Phthalate and Triclosan Levels Have Opposing Associations With Risk Factors for Gestational Diabetes Mellitus

Abstract: Certain phthalates and bisphenol A (BPA) have been associated with insulin resistance and type 2 diabetes in non-pregnant adults, but studies of gestational diabetes mellitus (GDM) have reported conflicting results for phthalates and no associations with BPA. Our aim was to investigate the relationship between maternal serum levels of phthalate metabolites and phenols at 10–17 weeks of gestation and glucose homeostasis at 28 weeks of gestation. 232 women aged ≥16 years without type 1 or 2 diabetes with singlet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(26 citation statements)
references
References 53 publications
1
25
0
Order By: Relevance
“…Our findings regarding high urinary levels of MEHP in non-diabetic women compared to GDM patients are similar to the results found in the Cambridge Baby Growth Study subcohort, where no positive associations between MEHP serum levels and GDM were found. However, positive associations between MEHP serum levels with 120-min plasma glucose in women without GDM [62] were found. In another study performed in a cohort of pregnant women in China, MEHP exposure levels were correlated with fasting blood glucose levels in the third trimester of pregnancy in non-diabetics but not in women with GDM [36].…”
Section: Discussionmentioning
confidence: 99%
“…Our findings regarding high urinary levels of MEHP in non-diabetic women compared to GDM patients are similar to the results found in the Cambridge Baby Growth Study subcohort, where no positive associations between MEHP serum levels and GDM were found. However, positive associations between MEHP serum levels with 120-min plasma glucose in women without GDM [62] were found. In another study performed in a cohort of pregnant women in China, MEHP exposure levels were correlated with fasting blood glucose levels in the third trimester of pregnancy in non-diabetics but not in women with GDM [36].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, several groups assessed the effect of phthalate exposure on glycemia, hypertensive, and vitamin D homeostasis during pregnancy and hypothesized that the effect may associate with pregnancy complications, including GDM and pregnancy-induced hypertensive diseases (42)(43)(44)(45)(46)(47)(48)(49)(50)(51)(52)(53)(54). So it is important to characterize the potential risk of phthalate exposure during pregnancy.…”
Section: Prenatal Phthalate Exposure and Complication Of Pregnancymentioning
confidence: 99%
“…It was reported that phthalate exposure led to a loss and an abnormal ultrastructural pattern of β cells in the pancreas, thereby reducing the insulin content and altering blood glucose levels (55). To date, a lot of epidemiological research had evaluated the associations between maternal phthalate exposure and gestational glycemia levels (42)(43)(44)(45)(46), but there was not enough evidence to draw a definitive conclusion.…”
Section: Prenatal Phthalate Exposure and Gestational Diabetes Mellitusmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, BPA urinary levels at the second trimester of pregnancy were positively associated with post-load glycaemia levels [94]. However, other cohort studies did not confirm the association between EDCs exposure and IGT, showing contrasting results for both BPA [95][96][97][98][99] and phthalates [97]. A possible reason for these controversial outcomes lies in the confounding effect of adiposity.…”
Section: Impact On the Mother And Risk Of Gdmmentioning
confidence: 99%